Anxiety and depression intensity and the quality of life of patients with an implanted pacemaker - Kamil Sikora; Robert Jan Łuczyk; Agnieszka Wawryniuk; Marta Łuczyk; Agnieszka Zwolak (Kazimierz Wielki University, 2021)
Introduction. The consequences of anxiety and depression in various forms affect the course of cardiovascular diseases - including patients with an implanted pacemaker. To improve the quality of care for such patients, it is important to understand the scale of the problem, as well as to determine the impact of the above-mentioned symptoms on the patients' quality of life. Aim of research. The aim of the study was to assess the relationship between the quality of life and the anxiety and depression intensity on patients with implanted pacemakers. Material and methods. The study involved 100 patients hospitalized at the SPSK 4 cardiology clinic in Lublin with an implanted pacemaker. The method of diagnostic survey and research tools were used - the WHOQOL - Bref questionnaire to assess the quality of life and the Hospital Anxiety and Depression Scale (HADS-M). The results of the research are summarized in the statistical analysis. Results. The average score obtained by the respondents on the depression scale was 6.05 points with a standard deviation of 4.47. On the anxiety scale, this result was 7.99 points with a standard deviation of 4.54. The results indicating disorders in both scales concern values higher than or equal to 11 points. On the depression scale they were obtained by 16% of the respondents, while on the anxiety scale 26%. The conducted analyses showed a statistically significant relationship between the level of anxiety and depression and the quality of life of the respondents in all domains. The overall declared quality of life of the respondents and the self-esteem of the health condition were the lower, the higher the anxiety and depression severity coefficient in the study group. Conclusions.1. Most of the studied patients with pacemakers do not have high levels of anxiety and depression. 2. The occurrence of anxiety and depression affects the quality of life of respondents after pacemaker implantation in all domains. 3. Patients with high levels of anxiety and depression have a lower assessment of their quality of life and health.